Faktor-faktor yang Mempengaruhi Praktik-praktik Pengungkapan Sosial: Studi pada Perusahaan-perusahaan High Profil yang Terdaftar di Bursa Efek Jakarta - Pratiwi, Maharani Suendaryanti; Djamhuri, Ali (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2004)
The purposes of this study are to find out whether corporate size, profitability, and public share ownership influence social disclosure practices in annual report; and to find out which one of those independent variables give the most effect on social disclosure practice in annual report. Using 102 annual reports 2002 of high-profile corporates listed in Jakarta Stock Exchange, this study found that corporate size, profitability, and public share ownership give a significant effect to social disclosure practices in annual report in a simultaneous way. But in partial way, only corporate size gives a significant effect to social disclosure practice in annual report.Keywords: social disclosure, corporate size, profitability, and public share ownership.